PROGRAMA MATEMATIS PENYELESAIAN MASALAH PROJECT CRASHING - Irawati Irawati; Abdullah Shahab (Jurnal Teknobisnis, 2006)
The determination of project accomplishment time is tedious and time consuming. This problem is aggravated in a project with a plenty of activities exhibiting intricate interdependency among activities. The determination of project completion time, in general, is done manually using methods such as CPM or PERT. In case where the project is to be completed earlier than scheduled, the determination of activities, which are capable to be crashed, entails a new problem in a project management. A mathematical model is here proposed to solve the problem in a faster and a more accurate way. The solution could be obtained easier with the advantage of having the ability to specify optimally the activities that could be compressed to complete the project in a scheduled time with a minimum cost. The model is then applied in a project of ship maintenance with a procurement of normal and crash data time and cost. The solution of the model indicates which activities, and time requirement, could be compressed in order to complete the project in a scheduled time with a minimum cost. The model could be naturally applied to various projects.